Software design for unmanned surface vehicles - Lim, Jie Han (2016)
As the trend of technology now focuses on the potential of artificial intelligence and autonomous, the development of unmanned vehicle had become one of the greatest interest for military and research purposes. As part of the development of unmanned surface vehicle for Maritime RobotX Challenge 2016, the project aims to develop a reliable control system for the USV. To create a reliable control system for the USV, the project focuses on the development of digital control propulsion system and the development of data transmission system for the onboard computer to connect with each microcontroller and sensing module. These include the design, modification and implementation of hardware and software architecture. The development of digital control propulsion system is achieved by modifying the manually operated motor with Arduino microcontroller and digital potentiometer while the development of data transmission system is realized by implementing Java software application with serial communication function. The development process consists of several stages as testing and troubleshooting is required throughout the project.